2009
DOI: 10.1016/j.jtcvs.2009.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-reactive protein levels to predict early and late mortalities after coronary artery bypass surgery: Eight years of follow-up

Abstract: Preoperative C-reactive protein levels can be used in risk stratification in coronary artery bypass grafting surgery. A C-reactive protein level greater than 10 mg/L is a risk factor for early mortality, whereas a level greater than 5 mg/L is a risk factor for late mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…There is a limited amount of research that has used acute surgery as an outcome measurement, and the use of biomarkers for risk prediction in surgery is generally directed towards predicting post-operative outcomes, such as morbidity and mortality [ 24 , 25 ]. A British study found associations between increasing CRP levels during admittance and the risk of undergoing acute surgery in patients presenting with acute renal colic.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited amount of research that has used acute surgery as an outcome measurement, and the use of biomarkers for risk prediction in surgery is generally directed towards predicting post-operative outcomes, such as morbidity and mortality [ 24 , 25 ]. A British study found associations between increasing CRP levels during admittance and the risk of undergoing acute surgery in patients presenting with acute renal colic.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In cardiac surgery field, several investigators evaluated the impact of preoperative CRP level on postoperative outcomes. [6][7][8][9][10][11]14 Cappabianca et al 14 suggested a value of 0.5 mg/dL or greater as a predictor of in-hospital mortality, postoperative infection, and midterm mortality. They included 597 patients with all types of cardiac procedures including on-pump/off-pump coronary bypass surgery and valvular and aortic root surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In coronary artery bypass grafting (CABG) field, increased preoperative CRP has been reported as an independent predictor of early and long-term mortality as well as early graft occlusion. [6][7][8][9][10][11] Most studies evaluating the relation between preoperative CRP and postoperative clinical outcomes focused on on-pump CABG. Conventional on-pump CABG using cardiopulmonary bypass (CPB) and cardiac arrest has diverse range of perioperative inflammatory reaction that may affect postoperative adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation has been proposed to have an important role in determining early postoperative complications (eg, low‐output syndrome, myocardial injury, and atrial fibrillation or stroke). Indeed, increased preoperative CRP (C‐reactive protein) levels are independently associated with early and late mortality in CABG patients 24. In other studies, preoperative levels of IL‐6, IL‐8, and MCP‐1 (monocyte chemoattractant protein 1) predict postoperative atrial fibrillation development in CABG patients 25.…”
Section: Differences In Systemic Inflammatory Reaction and Platelet/cmentioning
confidence: 95%